The emerging role of exosome-derived non-coding RNAs in cancer biology. (1st February 2018) - Fan, Qing; Yang, Liang; Zhang, Xiaodong; Peng, Xueqiang; Wei, Shibo; Su, Dongming; Zhai, Zhenhua; Hua, Xiangdong; Li, Hangyu
Abstract: Exosomes are a new means of intercellular information exchange that have aroused great research interest. Long neglected in research, exosomes were deemed nonfunctional cellular components to be discarded. However, it has been gradually revealed that exosomes are an important tool for the exchange of intercellular information and material. Exosomes contain specific repertoires of non-coding RNAs (ncRNAs, including microRNA and lncRNA), indicating that a specific RNA sorting mechanism may exist. Correspondingly, intracellular multivesicular bodies (MVBs) are produced after fusion with the cell membrane to release exosomes rather than inducing autophagy, which reveals that there may be a specific regulatory mechanism for MVB secretion. Cells can trigger cancer-related disorders after the recognition and uptake of circulating exosomal ncRNAs, providing indications for early tumor biopsy and treatment. The use of exosomes as a biological carrier in targeted therapy has been demonstrated. However, there may be a specific, unknown switch for loading drugs. This review focuses on the mechanisms of exosome biogenesis, release, and uptake. We also review the promotion of tumor development by exosomal ncRNAs including chemotherapy resistance, metastasis and the prospective use of exosomes in cancer diagnosis and treatment. Highlights: We summarize mechanisms for the biogenesis, release and uptake of exosomes. MVBs fate may contain a specific regulatory mechanism on autophagy and exosomes secretory. Exosomal ncRNAs play a vital role in cell to cell communication to promote tumor progression. Exosomes may be a promising application in cancer diagnosis and treatment.